2005
DOI: 10.1203/01.pdr.0000157726.65492.cd
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intrauterine Growth Restriction on the Number of Cardiomyocytes in Rat Hearts

Abstract: Epidemiologic studies have linked intrauterine growth restriction (IUGR) with an increased incidence of cardiovascular disease later in life; reduced cardiomyocyte number in IUGR hearts may underlie such prenatal programming. Our aim was to examine the effect of IUGR, as a result of maternal protein restriction, on the number of cardiomyocytes in the rat heart at birth. Rats were fed either a low-protein diet (LPD) or a normal-protein diet (NPD) during pregnancy. At birth, the offspring were killed and the hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
160
4
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(196 citation statements)
references
References 39 publications
(33 reference statements)
23
160
4
3
Order By: Relevance
“…A significant reduction in the proportion of terminally differentiated cardiomyocytes has been shown in fetal sheep models of IUGR (Bubb et al, 2007;Morrison et al, 2007). In addition, recently, we have shown that the number of cardiomyocytes is significantly reduced at birth in rat offspring that had been exposed to maternal protein restriction (Corstius et al, 2005). As cardiomyocytes continue to proliferate in rats for a further one to 2 weeks after birth (Li et al, 1996), it is important to extend our previous studies and examine the number of the cardiomyocytes in the heart of growth restricted offspring at a time-point when the cardiomyocytes are terminally differentiated and have ceased proliferating.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…A significant reduction in the proportion of terminally differentiated cardiomyocytes has been shown in fetal sheep models of IUGR (Bubb et al, 2007;Morrison et al, 2007). In addition, recently, we have shown that the number of cardiomyocytes is significantly reduced at birth in rat offspring that had been exposed to maternal protein restriction (Corstius et al, 2005). As cardiomyocytes continue to proliferate in rats for a further one to 2 weeks after birth (Li et al, 1996), it is important to extend our previous studies and examine the number of the cardiomyocytes in the heart of growth restricted offspring at a time-point when the cardiomyocytes are terminally differentiated and have ceased proliferating.…”
Section: Introductionmentioning
confidence: 71%
“…The blocks were exhaustively sectioned at 20 lm using a Leica RM2165 supercut microtome (Leica Corp., Nusstoch, Germany). Every fortieth section was collected (with the first section between 1 and 40 chosen at random) and stained with hematoxylin in a 1000-W microwave (50% power for 2.5 min) (Corstius et al, 2005).…”
Section: Tissue Processing and Measurement Of Heart Weight And Ventrimentioning
confidence: 99%
See 1 more Smart Citation
“…(Nikon Instruments). Cardiac tissue volume and cardiomyocyte number were determined by using stereological investigations as described (46). Ventricle wall thickness was assessed by measuring the thickness of the wall at the point perpendicular from the center of the longest axis of the ventricle.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, it could be shown that IUGR is associated with a reduced number of cardiomyocytes at the time of birth (4). Moreover, fetal hypoxia, a frequent cause of IUGR, resulted in early alterations of myocardial vasculature and changes in cardiac structure and function resembling dilated cardiomyopathy in chicks (5).…”
mentioning
confidence: 99%